ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION AND FINANCIAL ORIENTATION IN SUPPORTING THE PERFORMANCE OF KARAWO SMEs IN GORONTALO CITY - Solikahan, Eka Zahra; Mohammad, Ali (Jurnal Aplikasi Manajemen, 2019)
This study aims to examine the influence of Entrepreneurial Orientation (EO), Market Orientation (MO), and Financial Orientation (FO) on the Performance of Karawo SMEs. The research design used was quantitative analysis by using multiple regression analysis tools. It was found that entrepreneurial orientation did not affect the performance of Karawo SMEs, market orientation did not affect the performance of Karawo SMEs. However, the finding regarding financial orientation was different. It found that market orientation influenced the performance of Karawo SMEs in Gorontalo City. Therefore, based on research findings obtained, to improve the performance of SMEs, further research can develop the existing models by adding two variables, namely customer value and strategy orientation, in improving SME performance. Also, SME performance should be classified into two parts, namely financial performance, and non-financial performance.